2020
DOI: 10.1002/elan.202060511
|View full text |Cite
|
Sign up to set email alerts
|

Electroactivated Disposable Pencil Graphite Electrode – New, Cost‐effective, and Sensitive Electrochemical Detection of Bioflavonoid Hesperidin

Abstract: In this paper, for the first time, electroactivated disposable pencil graphite electrode (ePGE) was used for the detection of bioflavonoid hesperidin with cyclic and differential pulse voltammetry. The electroactivation efficiency of the pencil graphite electrode (PGE) was examined employing electrochemical impedance spectroscopy (EIS) and scanning electrochemical microscopy (SECM) and the enhancement of electron transfer kinetics of the PGE after the electroactivation was found. Hesperidin is irreversibly oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Despite the fact that it was beyond the aim of our study to establish an exact mechanism for HESP voltammetric behavior at H type PGE, correlating the cyclic voltammetric results with the data existing in the literature [5,16,21,23,25], it was concluded that, also similar to diosmin [19], peak a2 was due to the irreversible oxidation of the guaiacol moiety (3 -OH, 4 -OCH 3 , the o-methoxyphenol group in ring B (Figure 1)) to o-benzoquinone. However, recent theoretical calculations regarding the relationship between the first anodic peak potential and the changes in the electronic structure of flavonoids pointed out that the electrochemical oxidation of these compounds, including HESP, start with the abstraction of an electron [39].…”
Section: Hesperidin Voltammetric Behavior At the Pencil Graphite Electrodementioning
confidence: 79%
See 3 more Smart Citations
“…Despite the fact that it was beyond the aim of our study to establish an exact mechanism for HESP voltammetric behavior at H type PGE, correlating the cyclic voltammetric results with the data existing in the literature [5,16,21,23,25], it was concluded that, also similar to diosmin [19], peak a2 was due to the irreversible oxidation of the guaiacol moiety (3 -OH, 4 -OCH 3 , the o-methoxyphenol group in ring B (Figure 1)) to o-benzoquinone. However, recent theoretical calculations regarding the relationship between the first anodic peak potential and the changes in the electronic structure of flavonoids pointed out that the electrochemical oxidation of these compounds, including HESP, start with the abstraction of an electron [39].…”
Section: Hesperidin Voltammetric Behavior At the Pencil Graphite Electrodementioning
confidence: 79%
“…The first electrochemical investigations of flavonoids were based on their reduction at mercury electrodes, but the presence of the hydroxyl groups in their structure enables also their electrooxidation. This was investigated since the 1980s, starting with the glassy carbon electrode (GCE) [16] and employing many other electrodes either bare [5,[17][18][19], electroactivated [20,21] or modified with different carbon based materials like carbon nanotubes [22][23][24] or graphene derivatives [25][26][27][28], nanomaterials [26,[28][29][30], polymeric films [27,28,31], etc. Unfortunately, most of the electrodes encounter problems due to the electroactive surface fouling during the electrochemical investigations, especially when these are based on the oxidation of phenolic compounds, which can generate phenoxy radicals able to polymerize and produce a film covering the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The slope of the equation was ~−0.053 V pH −1 , similar to the theoretical Nernstian slope of 0.059 V pH −1 . This parameter corresponded to an oxidation mechanism that included the exchange of an equal number of protons and electrons in the reaction [ 40 ].…”
Section: Resultsmentioning
confidence: 99%